ANALISIS PERENCANAAN PENGENDALIAN BAHAYA PADA SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) BERDASARKAN PP NO.50 TAHUN 2012 DI PT.X - Arif Setiawan; Ekawati Ekawati; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2017)
Occupational safety and health is the main requirement to win on free market competition.On Government Regulation no. 50 of 2012 regulates that every companies with certain conditions must implement Occupational Safety and Health Management System (OSHMS). PT. X has a Department of Occupational Safety and Health newly established in February 2013 therefore the regulation of SMK3 still on process development. This research aims to know the suitability of hazard control planning on OSHMS in PT. X based on Government Regulation No.50 of 2012.This research is a descriptive qualitative in-depth interviews. The subjects of this study consists of 4 people as the main informants and 2 as an informant triangulation. The result of research is indicated hazard control planning implemented by the company has been following the Government Regulation No. 50 of 2012, but there are three things that are not appropriate. There are some objects that cannot be measured  since there’s no indicators of measuring, several target activities have no indicators of achievement, 12 regulations and other requirements have not been applied. PT. X need to provide achievement indicators for each target that they are going as well as immediately apply regulations are not appropriate.